Performance-based policy in offender rehabilitation: Limitation or innovation for front-line workers in Liaison and Diversion services?. (September 2020) - Rocha, Paulo; Holmen, Ann-Karin
In recent years, the English government has been using competitive elements in the process of allocating public funds through policy. Front-line workers struggle with the limitations imposed by such a model. A qualitative case study was conducted to investigate the impact of a new performance-based policy on front-line workers of a public service called Liaison and Diversion. The findings demonstrated that professionals have been adapting the policy to local circumstances found at the street level. We argued that adaptation is a form of employee-based innovation that optimises the use of scarce resources and customises services to the clients.